Evaluation and Management of Deficiency of Adenosine Deaminase 2: An International Consensus Statement - Lee, Pui Y.; Davidson, Brad A.; Abraham, Roshini S.; Alter, Blanche; Arostegui, Juan I.; Bell, Katherine; Belot, Alexandre; Bergerson, Jenna R.E.; Bernard, Timothy J.; Brogan, Paul A.; Berkun, Yackov; Deuitch, Natalie T.; et al. (American Medical Association, 2023)
Importance: Deficiency of adenosine deaminase 2 (DADA2) is a recessively inherited disease characterized by systemic vasculitis, early-onset stroke, bone marrow failure, and/or immunodeficiency affecting both children and adults. DADA2 is among the more common monogenic autoinflammatory diseases, with an estimate of more than 35000 cases worldwide, but currently, there are no guidelines for diagnostic evaluation or management. Objective: To review the available evidence and develop multidisciplinary consensus statements for the evaluation and management of DADA2. Evidence Review: The DADA2 Consensus Committee developed research questions based on data collected from the International Meetings on DADA2 organized by the DADA2 Foundation in 2016, 2018, and 2020. A comprehensive literature review was performed for articles published prior to 2022. Thirty-two consensus statements were generated using a modified Delphi process, and evidence was graded using the Oxford Center for Evidence-Based Medicine Levels of Evidence. Findings: The DADA2 Consensus Committee, comprising 3 patient representatives and 35 international experts from 18 countries, developed consensus statements for (1) diagnostic testing, (2) screening, (3) clinical and laboratory evaluation, and (4) management of DADA2 based on disease phenotype. Additional consensus statements related to the evaluation and treatment of individuals with DADA2 who are presymptomatic and carriers were generated. Areas with insufficient evidence were identified, and questions for future research were outlined. Conclusions and Relevance: DADA2 is a potentially fatal disease that requires early diagnosis and treatment. By summarizing key evidence and expert opinions, these consensus statements provide a framework to facilitate diagnostic evaluation and management of DADA2.
Keywords: General Medicine